2020
DOI: 10.5194/esurf-2020-23
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new workflow for the automated measurement of shape descriptors of rocks

Abstract: Shape properties of rocks carry important geological information about their origin, and they may also provide a window to study the abrasion processes forming their geometry. The number of mechanical equilibria is a significant property with a profound mathematical background that could reveal the secrets hidden in the artifacts of Nature. Although it is easy to count by hand, the automation of its measurement is not a straightforward task. A new workflow is introduced for the fast and efficient measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We will show in Section "Benchmark" that the size limit of a sample for Structure Sensor Mark I. was 1,000 mm 3 . A video demonstration of the new method is available at Fehér et al, (2020).…”
Section: Hardwarementioning
confidence: 99%
“…We will show in Section "Benchmark" that the size limit of a sample for Structure Sensor Mark I. was 1,000 mm 3 . A video demonstration of the new method is available at Fehér et al, (2020).…”
Section: Hardwarementioning
confidence: 99%
“…Tunwal et al (2020) proposed image-based automated particle shape analyses for both consolidated and loose sediments which can measure traditional, mathematically complex and common geometric shape parameters. Fehér et al (2020) demonstrated the effectiveness of 3D laser scanning of beach pebbles by comparing the results with a hand-measured set of pebbles. Thus, advances in technology are making automatic extraction of shape parameters possible.…”
Section: Introduction 1a Brief History Of Shape Indicesmentioning
confidence: 99%